μ-GLANCE: A Novel Technique to Detect Chromatically and Achromatically Lensed Gravitational-wave Signals - Aniruddha Chakraborty; Suvodip Mukherjee (The Astrophysical Journal)
Gravitational microlensing in the wave-optics (WO) regime occurs when the Schwarzschild radius of a lensing object is comparable to or smaller than the wavelength of incoming gravitational waves (GWs), producing chromatic amplitude and phase modulations. In contrast, geometric-optics effects happen when wavelength is much smaller than the lensing object, leading to frequency-independent amplifications and phase shifts. GWs can undergo both effects of lensing owing to interactions with objects of different scales. To detect and characterize the WO features from a lensed GW, we have developed a novel method, μ -GLANCE (Micro-Gravitational Lensing Authenticator using Non-modeled Cross-correlation Exploration). In this technique, we calculate the cross-correlation between the residuals from different detectors. We assign a false-alarm rate to each potential WO microlensed candidate from a statistical viewpoint, depending on how many times the noise cross-correlation matches the strength of the residual cross-correlation of the candidate over a certain period of time. We show that for an event with a matched-filtering signal-to-noise ratio close to 30, a residual due to WO lensing with an amplitude about 10% of magnification μ  ≈ 3.2 will start to show deviation from the noise distribution at more than a 68% confidence interval with the LIGO-Virgo-KAGRA sensitivity for the fourth observation run. This method provides the first technique to detect geometric-optics and WO effects from a WO microlensed GW without assuming any specific lensing model, and its application to the current and future GW data can identify events with both chromatic and achromatic lensed scenarios.